2013
DOI: 10.1002/ana.23838
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic stroke is associated with the ABO locus: The EuroCLOT study

Abstract: ObjectiveEnd-stage coagulation and the structure/function of fibrin are implicated in the pathogenesis of ischemic stroke. We explored whether genetic variants associated with end-stage coagulation in healthy REFVIDunteers account for the genetic predisposition to ischemic stroke and examined their influence on stroke subtype.MethodsCommon genetic variants identified through genome-wide association studies of coagulation factors and fibrin structure/function in healthy twins (n = 2,100, Stage 1) were examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
100
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 138 publications
(106 citation statements)
references
References 43 publications
3
100
2
1
Order By: Relevance
“…Previous genome-wide association studies (GWAS) in predominantly European-ancestry groups have identified ten loci robustly associated with stroke 312 . In most instances, the associations with stroke were attributed to individual subtypes of ischemic stroke, such as LAS 5,8,9 , CES 3,4 , and SVS 10,12 , or of ICH 6 , although some loci were associated with two or more stroke subtypes 7,9,11,13 or with any stroke 10 . We hypothesized that combining a substantially larger sample size with a transancestral analytic approach would identify additional risk loci and improve fine mapping of causal variants.…”
mentioning
confidence: 98%
“…Previous genome-wide association studies (GWAS) in predominantly European-ancestry groups have identified ten loci robustly associated with stroke 312 . In most instances, the associations with stroke were attributed to individual subtypes of ischemic stroke, such as LAS 5,8,9 , CES 3,4 , and SVS 10,12 , or of ICH 6 , although some loci were associated with two or more stroke subtypes 7,9,11,13 or with any stroke 10 . We hypothesized that combining a substantially larger sample size with a transancestral analytic approach would identify additional risk loci and improve fine mapping of causal variants.…”
mentioning
confidence: 98%
“…Four of these loci have P values reaching genome-wide significance in the large METASTROKE Consortium, the largest GWAS of IS to date, and all 4 genome-wide significant associations were subtype specific: 4q25 ( PITX2 ) and 16q22 ( ZFHX3 ) with cardioembolic stroke, 43,44 7p21 ( HDAC9 ) and 6p21 with large artery atherosclerotic stroke. 15,45,46 Two additional loci, that is, the 9p21 locus ( CDKN2B-AS1 ) with large artery atherosclerotic stroke 45,47,48 and 9q34 locus ( ABO ) with total IS, large artery atherosclerotic stroke, and cardioembolic stroke 49 did not reach genome-wide significance but were robustly replicated in other studies, albeit with small effect sizes. Notably, 1 locus, NINJ2 (12p13), which was initially identified in population-based cohort studies to be associated with all IS, has not been replicated in well-powered hospital-based case–control studies.…”
Section: Methodsmentioning
confidence: 85%
“…52,53 Last, the ABO locus, which was initially identified by GWAS associated with the clotting trait (ie, von Willebrand factor), was associated with cardioembolic and large artery atherosclerotic strokes. 49 However, little is known about the biological relevance of HDAC9 and the 6p21 locus to the large artery atherosclerotic stroke. HDAC9 encodes histone deacetylase 9 and may affect transcriptional regulation by altering chromosome structure.…”
Section: Methodsmentioning
confidence: 99%
“…A LocusZoom plot 21 is displayed in Figure S4. A total of 9 variants at the chr 1 locus were significant at the 1 × 10 −9 level, including two index SNPs previously associated with D-dimer in European GWAS (rs12029080 18 , rs2022309 22 ). However, none of these variants remained significant after conditioning on the lead variant rs2022030 (Figure S5a).…”
Section: Resultsmentioning
confidence: 99%